2012
DOI: 10.2478/s11536-011-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Computerised static posturography in neurology

Abstract: AbstractPosturography is a general term for techniques used to measure postural stability on static or dynamic measuring platforms. The principle of static computerised posturography (SCPG) is the detection of the centre of foot pressure (CFP) in upright stance on a posturography platform. Our communication deals with the importance of SCPG in differential topodiagnosis of vestibular syndromes in neurology. The set of examinations and evaluations carried out was divided among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…A study also states that t posturography is a valuable auxiliary test for balance disorders, especially given the lack of more suitable tests. According to our results, SCPG can be used for a rough differential topodiagnosis of balance disorders in neurology [13].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…A study also states that t posturography is a valuable auxiliary test for balance disorders, especially given the lack of more suitable tests. According to our results, SCPG can be used for a rough differential topodiagnosis of balance disorders in neurology [13].…”
Section: Resultsmentioning
confidence: 61%
“…Posturography is a general term for techniques used to measure postural stability on static or dynamic measuring platforms. The principle of static computerised posturography (SCPG) is the detection of the centre of foot pressure (CFP) in upright stance on a posturography platform [13].…”
Section: Resultsmentioning
confidence: 99%
“…Bougard et al reported that postural control shows diurnal fluctuations and is better in the evening. However, they did their work only in 19 healthy controls [12]. Degache et al used SPG and reported that nocturnal respiratory disturbances affect postural stability during the day.…”
Section: Discussionmentioning
confidence: 99%
“…Posturography, also known as a balance test, allows the evaluation of postural stability on static and dynamic platforms. The basic principle of static posturography (SPG) is the measurement of changes in centre of foot pressure on a stationary platform [12]. SPG helps to assess the effects of visual, vestibular, and somatosensory inputs on postural control effectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…Posturografija yra neabejotinai naudingas tyrimo metodas vestibulinės sistemos sutrikimų diferencinėje diagnostikoje ir gydymo efektyvumo vertinime [12,16,17,18,33]. VUL SK ANG ligų centre posturografijos tyrimas "Tetrax" yra naudojamas nuo 2014 metų ir galime teigti, kad ši sistema yra vertinga klinikinėje praktikoje, ypač diferencijuojant periferinės vestibulinės sistemos sutrikimus nuo kitų sistemų (centrinės, somatosensorinės, psichiatrinės, ortopedinės), kas ir yra kol kas pirmiausia ir svarbiausia renkantis tolesnę gydymo taktiką; sistema įgalina objektyviai greitai ir dažnai vertinti ligos dinamiką, vaistų ir reabilitacijos efektyvumą, o tai iki šiol buvo subjektyvu.…”
Section: Išvadosunclassified